The Spectrum of RS Ophiuchi during the 1958 maximum - Gratton, Livio (1961)
The recurrent Nova RS Oph brightened to the 6th magnitude between July 13 and 14 1958. This is the third observed outburst of this variable; the other two occurred in 1898 and 1933 (Cecchini and Gratton 1941). The news of the outburst reached Córdoba the 15th of July and a dozen of spectroscopic plates were obtained by the Authors from July 15.9 to July 25.0 at Bosque Alegre with the standard equipment ( 60" Reflector, grating spectrograph with a dispersion of 42 A/mm). Buring the time of the observations, apparently, the star reached a maximum (around July 18) and began to fade slowly. (Párrafo extraído a modo de resumen)